Peningkatan Kinerja Guru melalui Supervisi Akademik di SDN 2 Pengkelak Mas - Mulhizin, Mulhizin (Lembaga Yasin AlSys, 2022)
The research conducted is a school action research (PTS) which raises questions about how teachers can improve their performance in the learning process in the classroom and the evaluation is carried out through ongoing mentoring activities for the school principal. This school action research activity was carried out at SDN 2 Pengkelak Mas for 3 months, from January to March 2021 by going through cycle stages. The purpose of this school action research (PTS) is to find out to what extent academic supervision is carried out by the principal followed by providing guidance/treatment of target teachers can improve the teacher's competency in classroom learning. In school action research (PTS) this was carried out in 2 cycles, the results of the actions taken proved to be able to improve teacher performance by achieving ideal standards. In cycle I, the increase in teacher competence after classroom supervision after ongoing coaching only reached around 66.67%, in cycle II it could increase to 100%. The average score obtained after class supervision in cycle I was 63.30 and increased in cycle II to 83.33, meaning that there was an increase of 20.03 and the level of completeness as a group/classical in cycle I reached 66.67% and in cycle II increased to 100%. The results of this school action research show that coaching/assistance in the academic supervision of school principals can improve teacher performance.